Pyogenic Liver Abscess Correlates With Increased Risk of Acute Pancreatitis: A Population-Based Cohort Study - Lai, Shih-Wei (J Epidemiol, 2015)
BACKGROUND: The aim of this study was to explore whether there is a relationship between pyogenic liver abscess (PLA) and subsequent risk of acute pancreatitis in Taiwan. METHODS: Using inpatients claims data from the Taiwan National Health Insurance Program, we identified 30 866 subjects aged 20–84 years with the first-attack of PLA from 2000 to 2010 as the PLA group and randomly selected 123 464 subjects without PLA as the non-PLA group. The incidence of the first attack of acute pancreatitis at the end of 2010 and the risk associated with PLA and other comorbidities were measured. RESULTS: The overall incidence of acute pancreatitis was 3.84-fold greater in the PLA group than in the non-PLA group (4.61 vs 1.19 events per 1000 person-years; 95% CI, 3.43–4.29). After controlling for potential confounding factors, the adjusted hazard ratio of acute pancreatitis was 3.00 (95% CI, 2.62–3.43) for the PLA group, as compared to the non-PLA group. Further analysis showed that compared to subjects with neither PLA nor comorbidities, patients with PLA and hypertriglyceridemia, biliary stones, alcoholism, or hepatitis C had greater risk of acute pancreatitis than those with PLA alone. CONCLUSIONS: PLA correlates with increased risk of subsequent acute pancreatitis. Comorbidities, including hypertriglyceridemia, biliary stones, alcoholism, and hepatitis C, may enhance the risk of developing acute pancreatitis.